THE EFFECT OF ADMINISTERING MANGOIS (Garcinia mangostana L.) SKIN EXTRACT IN DRINKING WATER ON ORGANOLEPTIC QUALITY BROILER MEAT - M. R. T. B., Girsang; Astawa, I P. A.; Sumardani, N. L. G. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study aims to determine the effect of administering mangosteen rind extract (Garnicia mangostana L.) in drinking water on the organoleptic quality of broiler meat. The design used in this study was a completely randomized design (CRD) with 4 treatments and 4 replications assessed by 15 semi-trained panelists and analyzed by Kruskal Waliss and Mann-Whitney statistics. The four treatments are: P0 (drinking water without mangosteen rind extract as a control), P1 (1% mangosteen rind extract in drinking water), P2 (2% mangosteen rind extract in drinking water), and P3 (3% extract mangosteen peel in drinking water). The variables observed were color, aroma, texture, tenderness, taste and overall acceptability. The results of the study showed that administration of 1%, 2%, 3% mangosteen rind extract via drinking water on the organoleptic quality of broiler meat was significantly different (P<0.05) on color, aroma, tenderness and overall acceptability and was not significantly different. (P>0.05) on taste. Based on the results of this research, it can be concluded that giving 1% mangosteen rind extract in drinking water can increase the tenderness of broiler meat, and giving 3% can increase the bright color of the meat, and the meat's aroma is not fishy. The best results when giving 3% are seen from the overall acceptance variable which includes color, aroma and tenderness.